2020
DOI: 10.1111/1346-8138.15479
|View full text |Cite
|
Sign up to set email alerts
|

Frequent brain metastases during treatment with BRAF/MEK inhibitors: A retrospective single institutional study

Abstract: Recent clinical trials revealed that both immune checkpoint inhibitors (ICI) and BRAF/MEK inhibitors significantly prolonged survival in melanoma patients when used for both advanced stage disease and postoperative adjuvant therapy. Although BRAF/MEK inhibitors are associated with a higher objective response rate than ICI, most patients relapse during treatment. However, progression patterns during treatment with BRAF/MEK inhibitors have not been extensively investigated. Here, we retrospectively collected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Forty-six full-text articles with the outcomes of interest (e.g., proportion and risk factors of MBM) were evaluated, and seven were excluded due to duplication or presenting results on the same population. A total of 39 articles were included in this SLR, and 38 full-text articles were extracted for the proportion results [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Among of them, 29 studies included patients with MBM at diagnosis (Stage IV) ( Supplementary Table S1 ) and 9 studies reported MBM proportion with brain metastasis occurring after diagnosis ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six full-text articles with the outcomes of interest (e.g., proportion and risk factors of MBM) were evaluated, and seven were excluded due to duplication or presenting results on the same population. A total of 39 articles were included in this SLR, and 38 full-text articles were extracted for the proportion results [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Among of them, 29 studies included patients with MBM at diagnosis (Stage IV) ( Supplementary Table S1 ) and 9 studies reported MBM proportion with brain metastasis occurring after diagnosis ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, frequent brain imaging during treatment with B-raf/MEK inhibitors seems warranted in order to detect early brain involvement and to promptly administer an immune checkpoint inhibitor in combination with local radiation therapy or surgery. 8 Our case may suggest that it might somewhat farfetched to proclaim that cures and long-term survival can be achieved with single agents B-Raf inhibitors in patients with metastatic melanoma. We believe that long-term responders to B-Raf inhibitors with or without MEK inhibition should be monitored very closely clinico-radiologically for a potential relapse.…”
mentioning
confidence: 86%
“…In this setting, the disease is often refractory to second-line agents, and leads almost unequivocally to dismal outcomes. In addition, Nakamura et al 8 showed that brain metastasis-free survival in patients treated with B-Raf/MEK inhibitors was significantly shorter than in those treated with anti-PD1 antibody monotherapy. This suggests that development of brain metastases during treatment with B-raf/MEK inhibitors might be more frequent than during anti-PD1 antibody monotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the efficacy of BRAFi/MEKi therapy or immunotherapy may differ between Western and Eastern melanoma patients [ 94 ]. These findings are of particular relevance, for example, for the management of melanoma brain metastases, since it was observed that the development of metastases was significantly higher in patients treated with BRAFi/MEKi than in those treated with immune checkpoint inhibitors [ 95 ]. Hence, the use of immunotherapy should be considered as a first-line therapy for brain metastases [ 96 ].…”
Section: Targeted Therapy For Braf-mutated Melanomamentioning
confidence: 99%